Handgrip Strength: An Early Warning Sign for Mobility Decline? A Meta-Analysis of Diagnostic Accuracy Studies - R. Ifan Arief Fahrurozi; Rose Dinda Martini; Roza Mulyana; Fandi Triansyah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Mobility limitations significantly impact the quality of life of older adults. Early identification of individuals at risk is crucial for timely intervention. This meta-analysis investigates the diagnostic accuracy of handgrip strength (HGS) in predicting future mobility decline in older adults. Methods: A systematic search of PubMed, Scopus, and Web of Science was conducted for diagnostic accuracy studies published between 2018 and 2024, evaluating the ability of baseline HGS to predict incident mobility limitations in older adults (≥60 years). Mobility limitations were defined as difficulties in performing activities of daily living (ADLs) or instrumental activities of daily living (IADLs). The primary outcomes were sensitivity, specificity, and diagnostic odds ratio (DOR) of HGS for predicting mobility decline. A bivariate random-effects model was used to pool data. Results: Seven diagnostic studies with a total of 3,870 participants were included. The pooled sensitivity of HGS for predicting mobility decline was 0.72 (95% CI: 0.65-0.78), and the pooled specificity was 0.70 (95% CI: 0.66-0.74). The pooled DOR was 4.85 (95% CI: 3.21-7.32), indicating good discriminatory ability. Conclusion: This meta-analysis demonstrates that HGS has moderate sensitivity and specificity for predicting future mobility decline in older adults. HGS assessment can be a valuable tool for identifying individuals at risk, although further research is needed to determine optimal cut-off points and combine HGS with other risk factors for improved prediction.